Caracterización climatológica del sector Cumbijín, Cantón Salcedo, provincia de Cotopaxi, para la elaboración de la plataforma integrada de datos de la gestión Agropecuaria, 2018 - Chango Pastrano, Karla Estefany (2018)
The purpose of this research is the climatological characterization of Cumbijín sector on Salcedo Canton, Cotopaxi Province, it is a research project that will serve as an input so that later it can serve in the construction of the integrated data platform for Agricultural Management, which will allow the agricultural technician and farmer to optimize their productive undertakings according to the climatological characteristics of the sector. A database of precipitation and average monthly temperatures was established from 1990 to 2012, which were extracted from the INAMHI bibliographic files of the meteorological stations closest to the sector. The behavior of each variables at the period was analyzed study time, climograms were constructed, diagrams of Gaussen where propitious sowing times were settled down for the pastures, chocho, frejol, corn and potato according to the optimal climatic requirements that demand these crops. A climatological weighting method over parameters that help to qualify the risk of a productive project is proposed, which will allow to farmers to take into account the climate variations and the effects of these in their crops development when a productive entrepreneurship is stablished. The climatological study showed that Cumbijín sector has a semi-humid / dry thermal Meso climate, presenting the maximum temperatures in March and September and the minimum temperatures in June and July, the maximum rainfall in the months April and November and the minimum rainfall on the months of July and August.